Intikhab-e-Kalam: Faiz Ahmed Faiz - Faiz, Faiz Ahmed; Edited and introduced by Iftikhar Arif (Karachi Oxford University Press, 2017)
This book contains a selection of the poems of Faiz Ahmed Faiz MBE, the Urdu poet to gain the greatest International recognition. Faiz was a Founder of the Progressive Writers Movement but enlisted in the British Indian Army during World War II. In Pakistan he became a journalist and trade union leader and since he was indicted in the 1951 Rawalpindi Conspiracy Case, he spent a number of terms in jail. He was the winner of the Lenin Peace Prize in 1962. Faiz struggled to promote liberal and secular ideals. The lyrical quality of his poems was high and has been compared to that of Hafiz the Persian Master. This selection was published on the poet$1 (Bs birth centenary.s
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam: Faiz Ahmed Faiz